Pemeriksaan Kesehatan Siswa TK sebagai Upaya Deteksi Dini Permasalahan Kesehatan Anak - Siti Munawaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
The optimal growth and development of children hinge on their health, which serves as the primary foundation. Given their susceptibility to diverse diseases, it is imperative to safeguard the health of children. Early detection of potential health issues stands out as a crucial method for ensuring the well-being of children. This community service initiative aims to carry out health assessments for children enrolled in private kindergarten schools in Surakarta. The objective is to identify and address health problems in children at an early stage. Doctors conduct these health examinations for a total of 123 kindergarten students, comprising 72 males and 51 females across different levels. Beyond the physical examinations, doctors also deliver educational sessions on children's health concerns to individual students and their class teachers, with the intention of disseminating this information to the students' parents. The predominant health issue among students is dental caries, affecting 54% (67 students). Following this, issues such as ear hygiene, enlarged tonsils, and colds are sequentially observed. Through these health assessments, the hope is to detect various health problems early on and implement timely preventive measures to uphold the overall well-being of children.